Female existentialist freedom and self-becoming in Maybe in Another Life - Sanca Odigitria Manesanulu; Linusia Marsih (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
Patriarchal structures have long confined women to subordinate roles, and literature offers a space to examine such structures and women's responses to them. This study uses feminist literary criticism, guided by Simone de Beauvoir's feminist existentialist framework, to examine Hannah Martin's position as a woman and how her choices across two parallel life paths reflect her movement within that position, in Taylor Jenkins Reid's Maybe in Another Life (2015), a narrative built around a single decision that splits Hannah's life into two trajectories. The research addresses two questions, the conditions that shape Hannah's position as a woman, and how her choices reflect her movement within that position. The study applies four concepts from Beauvoir's framework, woman as the Other, freedom and choice, transcendence and immanence, and the social construction of feminine identity. The method is descriptive qualitative, with the novel as the primary data source and the researcher as the main instrument for collecting and interpreting narrations, dialogues, and character actions. The results show that before the novel's split, Hannah exists within conditions that position her as the Other, marked by relational dependence, economic instability, and surrendering decisions to fate. Across both paths, she moves toward self-direction and the claiming of her own subjecthood, though neither path concludes with complete freedom.